2013
DOI: 10.1089/neu.2012.2760
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Magnetic Stimulation-Electroencephalography Responses in Recovered and Symptomatic Mild Traumatic Brain Injury

Abstract: Mild traumatic brain injury (mTBI) may cause diffuse damage to the brain, especially to the frontal areas, that may lead to persistent symptoms. We studied participants with past mTBI by means of navigated transcranial magnetic stimulation (nTMS) combined with electroencephalography (EEG). Eleven symptomatic and 8 recovered participants with a history of single mTBI and 9 healthy controls participated. Average time from injury to testing was 5 years. The participants did not have abnormalities or signs of inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…None of them had, however, obvious structural lesions on the MRI. In the symptomatic group, stimulation of the dorsolateral prefrontal cortex elicited delayed peaks and increased amplitude of some of the TMS-EEG components [57]. In the asymptomatic group, stimulation of the same site elicited responses of shortened latency.…”
Section: Pathological Statementioning
confidence: 87%
“…None of them had, however, obvious structural lesions on the MRI. In the symptomatic group, stimulation of the dorsolateral prefrontal cortex elicited delayed peaks and increased amplitude of some of the TMS-EEG components [57]. In the asymptomatic group, stimulation of the same site elicited responses of shortened latency.…”
Section: Pathological Statementioning
confidence: 87%
“…Only studies conducted on humans aged over 18 years were included. One study was excluded because relevant TMS results were previously reported . Studies investigating both mTBI and sports concussions were included for review.…”
Section: Methodsmentioning
confidence: 99%
“…In the most recent study, brain responses were compared between conscious patients with mild brain injury and healthy awake subjects [55]. Results showed altered brain reactivity and connectivity in the former compared to the latter that may be related to compensatory mechanisms of recovery.…”
Section: Tms-eeg In Patients Recovering From Comamentioning
confidence: 99%